Formulation, optimization, and characterization of whey protein isolate nanocrystals for celecoxib delivery - Farooq, Muhammad Asim; Jabeen, Amna; Wang, Bo (Journal of microencapsulation, 2021)
Current study aimed to improve the solubility and release profile of the celecoxib for cancer application. However, the low water solubility of celecoxib limited its application for cancer chemotherapy. Hence, new drug delivery-based approaches are compulsory for the efficient delivery of hydrophobic celecoxib for chemotherapy. The celecoxib-loaded nanocrystals were prepared by anti-solvent precipitation-ultrasonication technique, and the formulation was optimised through various process parameters. The optimised formulation had an average particle diameter of 171.09 ± 6.23 nm, with a PDI of 0.123 ± 0.009 and high ZP −27.3 ± 0.2 mV. The optimised formulation was stable, had higher entrapment efficiency 97.26 ± 1.12%. The conformational changes in the denatured protein solution were detected through fluorescence spectroscopy. The transmission electron microscopy investigation showed rod-shaped nanocrystals morphology, and no chemical interactions were observed in optimised formulation through FTIR. The DSC and PXRD analysis exhibited an amorphous state of the freeze-dried formulation drug. Also, optimised nanocrystals enhance drug solubility around 26.01-fold, 15.51-fold and 19.08-fold in purified water, pH 6.8 and pH 7.4, and accomplish sustained drug delivery, respectively. It can be concluded that biopolymer-coated celecoxib nanocrystals might be potential drug delivery of hydrophobic molecules for cancer therapy.